Estimation of the Pores Dimensions of Intumescent Coatings for Increase the Fire Resistance of Building Structures. (2015) - Gravit, Marina; Gumenyuk, Vasiliy; Sychov, Maxim; Nedryshkin, Oleg
Abstract: The authors first examined the possibility of estimating the pore space coating of intumescent coatings for increase the fire resistance of building structures using the program "Video tests".